СУТНІСНИЙ ВИМІР ТА ОЦІНКА РІВНЯ МИТНОЇ БЕЗПЕКИ - Барановський, Олександр Іванович (Науковий журнал «Світ фінансів», 2017)
Барановський О. І. Сутнісний вимір та оцінка рівня митної безпеки. Розглянуто значення митної безпеки в забезпеченні різних сфер життєдіяльності держави. Визначено місце і роль митної безпеки в економічній (фінансовій) безпеці на різних рівнях управління. Наведено авторське бачення сутності і різновидів митної безпеки. Проаналізовано чинники, що зумовлюють наявний стан митної безпеки. Виявлено загрози митній безпеці. З’ясовано підходи та індикатори оцінки рівня митної безпеки. Барановский А. И. Сущностное измерение и оценка уровня таможенной безопасности. Рассмотрена значимость таможенной безопасности в обеспечении разных сфер жизнедеятельности государства. Определены место и роль таможенной безопасности в экономической (финансовой) безопасности на разных уровнях управления. Представлено авторское видение сущности и разновидностей таможенной безопасности. Проанализированы факторы, обуславливающие состояние таможенной безопасности. Выявлены угрозы таможенной безопасности. Определены подходы и индикаторы оценки уровня таможенной безопасности. Baranovskyi O. Essential measurement and evaluation of level of customs security. Introduction. Development of the foreign economic activities, increase of the competitiveness of national economy, the robust state budget filling, ensuring of the adequate protection of environment and health of the citizens, cultural and historical values, resistance to the contraband goods require observation of the national interests as well as interests of the legal entities, individuals and regions in the customs field. With regard to that there is an urgent necessity in adherence to the customs security principles. Purpose. The purpose of this paper is in explicitation of the substance of the customs security, defining of its types, clarification of the factors, which impacts its state, identification of the threats of the customs security and choosing of the indicators for its level evaluation. Results. Importance of the customs security in ensuring of functioning of the different spheres of state as well as current problems in such sphere are reviewed. The place and role of the customs security in economic (financial) security on the different levels of administration are defined. Author’s view of the substance and types of customs security is presented. Factors which impact current state of the customs security are analyzed. Threats to the customs security are identified. Approaches and indicators for evaluation of level of the customs security are stated. Conclusion. Customs security is reviewed as availability of the customs policy in the country; progressive development of customs affairs; creation of effective and actual customs environment; implementation of efficient customs regulation and control; improvement of quality and availability of customs services along with reduction of operational expenses for customs services; ensuring of customs border protection; adequate state of customs system; impossibility of breaking of the customs rules and crimes in customs sphere; minimization of customs risks; creation of attractive customs climate. Adherence to the above will support creation of the effective system of ensuring of the customs security, which requires further analysis of the area.